Genomic characterization of Peruvian Creole goats: insights into population structure and runs of homozygosity - Corredor Arizapana, Flor Anita (2025)
Peruvian Creole goats (PCGs) represent a unique genetic resource shaped by adaptation to diverse environments and traditional breeding practices. In this study, we performed a genomic analysis of six regional populations (Ancash, Ica, Lambayeque, Lima, Piura, and Tumbes) using high-density SNP genotype data. Principal component analysis revealed a moderate genetic structure, with the Ica population showing clear separation and northern populations exhibiting overlap. Runs of homozygosity were predominantly short, and specific regions on chromosome 6 were shared across populations. Inbreeding coefficients were generally low, with Ancash showing the highest values. Linkage disequilibrium decayed rapidly over genetic distance, especially in Piura, indicating higher genetic diversity. Estimates of effective population size revealed decreasing trends across populations, with Piura maintaining the largest recent population size. These findings offer valuable insights into the population structure of Peruvian Creole goats, providing guidance for conservation and sustainable breeding efforts.